Malaria epidemics in Colombia, 1970-2019 - Julio Cesar Padilla Rodríguez; Mario Javier Olivera; María Cristina Padilla Herrera; Edwin Pachón Abril (Revista da Sociedade Brasileira de Medicina Tropical, 2022)
ABSTRACT Background: Malaria has unstable transmission in Colombia and has variable endemic-epidemic patterns. This study describes the epidemiological characteristics of malaria epidemics registered in Colombia from 1970-2019. Methods: Data from 1979-2019 were collected from the National Public Health Surveillance System. The data was tabulated and pertinent descriptive analyses were carried out. Results: Fifteen malaria outbreaks and approximately five-year-long epidemic cycles were observed in Colombia during the study period. Conclusions: Malaria epidemics in Colombia present a five-yearly transmission pattern, mainly due to the increased vulnerability produced by seasonal population migrations in receptive areas with active transmission.